Numerical Implementation of the Multicomponent Potential Theory of Adsorption in Python Using the NIST Refprop Database (Communications in Computational Physics, 2018)
In this paper, we present a detailed numerical implementation of the multicomponentpotential theory of adsorption which is among the most accurate gas mixturesadsorption models. The implementation uses the NIST Refprop database to describefluid properties and applies to pure gases and mixtures in both subcritical andsupercritical regimes. The limitations of the model and the issues encountered withits implementation are discussed. The adsorption isotherms of CH4/CO2 mixture aremodeled and parameterized as implementation examples.